(untitled) (Research, Society and Development, 2021)
Felines have a high potential to produce numerous progenies and the most indicated birth control is the ovariohysterectomy surgical procedure. The procedure causes a postoperative pain process, so an effective protocol is needed to assess pain and control it. The study was conducted with 40 females, which were divided into three distinct groups that were given different analgesic protocols, consisting of dipyrone sodium isolated, dipyrone sodium associated with meloxicam and dipyrone sodium associated with tramadol hydrochloride. The objective of the research was to evaluate three analgesic protocols in order to verify the most effective and affordable one. It was observed that the three protocols are viable and effective, however, dipyrone associated with meloxicam showed greater pain control.